2020
DOI: 10.1186/s12889-020-08872-6
|View full text |Cite
|
Sign up to set email alerts
|

Low program access despite high burden of sexual, structural, and reproductive health vulnerabilities among young women who sell sex in Mombasa, Kenya

Abstract: Background: Across Sub-Saharan Africa, young women who sell sex (YSW) face institutional barriers in accessing sexual health and HIV prevention programs designed for female sex workers. In 2018, Kenya developed a national framework to guide service provision for YSW aged 14-24 years. To help inform the implementation of the framework, we estimated the burden of vulnerabilities related to the Sustainable Development Goals (SDGs related to health and gender equality) and program contact among YSW. Methods: We us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Violence, rape, including by gangs (often drug use related) was a key theme reported in focus groups with teenagers in Cape Town who had dropped out of school (Sawyer-Kurian et al, 2011 ), with many women saying they would not disclose rape, including gang rape, due to fear of the perpetrator or other gang members. Among young women who sell sex in Mombasa 30% and 29% respectively had experienced physical and sexual violence, yet there was little awareness of programmes providing support (Roberts et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Violence, rape, including by gangs (often drug use related) was a key theme reported in focus groups with teenagers in Cape Town who had dropped out of school (Sawyer-Kurian et al, 2011 ), with many women saying they would not disclose rape, including gang rape, due to fear of the perpetrator or other gang members. Among young women who sell sex in Mombasa 30% and 29% respectively had experienced physical and sexual violence, yet there was little awareness of programmes providing support (Roberts et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Robert et al ( 2020 ) To identify enablers and barriers in accessing HIV and SRH services among adolescent key population Mainly urban counties (Nairobi, Mombasa) and Kisumu (mixed rural and urban), Kenya Institutional: Violence and discrimination from HCWs HIV and SRH services 108 vulnerable adolescents aged 10–19: boys reporting same sex relations; girls engaging in sex work; and adolescents injecting drugs Qual: focus groups and interviews 28. Roberts et al ( 2020 ) To estimate the burden of vulnerabilities related to gender equality and extent of contact young sex workers have with programmes to support them. Sex worker venues in Mombasa, Kenya Interpersonal: Physical and sexual None 408 young women aged 14–24 who sell sex Quant: survey 29.…”
Section: Methodsmentioning
confidence: 99%
“…These findings concur with findings elsewhere that found low contraceptive use among non-PrEP-seeking FSWs within this age group ( 16 , 27 , 28 ). Compared to older FSWs, younger FSWs, especially those in adolescence, experience poor access to HIV prevention and contraceptive services, have limited knowledge, and are more vulnerable to HIV transmission, unwanted pregnancies, and violence ( 29 ). In recognition of the unique needs of young key populations, including FSWs, in 2018, Kenya developed National Implementation Guidelines for HIV and STI Programming for Young Key Populations ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Kenya, even though the HIV prevention programme with FSWs has scaled up in the last decade [ 13 , 14 ], data from FSW programmes in Mombasa showed that the enrolment of FSWs <24 years was lower in the programme and among those enrolled, a higher proportion was lost at each service delivery step compared to their older counterparts [ 15 ]. Only 13.7% of the YWSS in the Transitions study reported contact with the local HIV prevention programme that was operational in the same venues where the study was conducted [ 16 ]. While there is evidence for effective interventions to prevent and treat HIV infections among adult FSWs [ 17 , 18 , 19 , 20 ], less is known about the delivery of these interventions with YWSS globally and in Africa [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…While there is evidence for effective interventions to prevent and treat HIV infections among adult FSWs [ 17 , 18 , 19 , 20 ], less is known about the delivery of these interventions with YWSS globally and in Africa [ 21 ]. There is need to use this existing evidence to prioritize YWSS in FSW interventions and adapt and evaluate effective interventions for FSWs to address the needs and priorities of YWSS [ 16 ].…”
Section: Introductionmentioning
confidence: 99%